Identifying research priorities with nurses at a tertiary children's hospital in the United Kingdom. (4th October 2016) - Williams, A.; Sell, D.; Oulton, K.; Wilson, N.; Wray, J.; Gibson, F.
Abstract: Aim: The objective of this study was to undertake a research priority setting exercise with the aim of maximizing efficiency and impact in research activity undertaken by nurses at one children's tertiary healthcare institution by ensuring the clinical staff directly shaped a coherent, transparent and consensus driven nurse‐led research agenda. Background: In Round 1, the research topics of 147 nurses were elicited using a modified nominal group technique as the consensus method. The number of participants in the 24 separate discussions ranged from 3 to 21, generating lists of between 6 and 23 topics. In Round 2, nurses from the clinical areas ranked topics of importance resulting in a set of four to five priorities. In Round 3, the divisional heads of nursing consulted with staff in all of their clinical areas to each finalize their five divisional priorities. The Nursing Research Working Group discussed and refined the divisions' priorities and voted on the final list to agree the top five research priorities for the organization. Results: A total of 269 research topics were initially generated. Following three rounds of ranking and prioritizing, five priorities were agreed at Divisional level, and from these, the five top organizational priorities were selected. These were (i) understanding and improving all aspects of the patient journey through the hospital system; (ii) play; (iii) staff wellbeing, patient care and productivity; (iv) team work – linking to a more efficient service; and (v) supporting parents/parent pathway. Conclusions: Divisional priorities have been disseminated widely to clinical teams to inform a patient‐specific nurse‐led research agenda. Organizational priorities agreed upon have been disseminated through management structures and processes to ensure engagement at all levels. A subgroup of the Nursing Research Working Group has been delegated to take this work forward so that the agreed priorities continue to contribute towards shaping nurse‐led research activity, thereby going some way to inform and embed an evidence‐based culture of inquiry.